Pengaruh Pendidikan Kesehatan Dengan Media Video Terhadap Pengetahuan Lem Pada Remaja Di MTS LKMD Giti Kec Kabun Kab Rokan Hulu - Rachman, Fikri Tamsir; Fitri, Dwi Elka; Aggreini, Silvia Nora (LPPM Sekolah Tinggi Ilmu Kesehatan Pekanbaru Medical Center, 2023)
Substances that have a fairly large impact that are often used among teenagers are inhalants (glues). Inhalants (glue) is part of an addictive substance which is a substance that is inhaled from an unstable (dissolved) place. Teenagers suck glue because of many factors, one of which is the lack of information about the risk of drug abuse against glue addicts which makes teens fall into glue sucking behavior. The purpose of this study was to determine the effect of health education using video media on adolescent knowledge about the dangers of glue addictive substance abuse in class VIII students at MTS LKMD Giti. This study used a pre-experimental (pre-experimental) research design with a one group prettest-posttest design. . The sampling technique used is Probability Sampling, namely simple random sampling (SRS). with a total of 64 respondents. The results showed that before being given health education, it was included in the less category, namely 56 respondents (87.5%). The results showed that after being given health education, most of the respondents were included in the good category, as many as 36 respondents (56.3%), so it can be concluded that health education has an effect on knowledge of the dangers of inhaling glue in adolescents at MTS LKMD Giti. It is hoped that respondents can implement health education using video media to increase knowledge among teenagers about the dangers of glue misuse